PentaFluoroStyrene-based block copolymers controlled self-assembly pattern: A platform paving the way to functional block copolymers. (5th October 2022) - Bosson, Karell; Marcasuzaa, Pierre; Bousquet, Antoine; Tovar, Günter E.M.; Atanasov, Vladimir; Billon, Laurent
Graphical abstract: Highlights: Diblock copolymers of 2, 3, 4, 5, 6-pentafluorostyrene (PFS) and butyl acrylate (BuA) synthesized by nitroxide mediated polymerization (NMP) with a large range of molar compositions and molecular weights. Nano-phase separation in thin films due to the high immiscibility of both polymeric blocks. Versatile self-assembly from out-of-the-plane PPFS to PBuA cylinders crossing through lamellar morphology. Functionalization of the PPFS block by para fluorine-thiol soft organo-catalysed substitution. Screening the nano-phase separation by matching the solubility parameters of the modified PFS and BuA monomer units. Abstract: Diblock copolymers of 2, 3, 4, 5, 6-pentafluorostyrene (PFS) and butyl acrylate (BuA) were synthesized by nitroxide mediated polymerization (NMP). By varying the conversion and/or the BuA monomer to PPFS macro-initiator ratio, various molar compositions of the block copolymer BCP were obtained. Due to the immiscibility of both polymeric blocks, phase separation at the nanometre scale occurred. The variety of BCP synthesized gave rise to a large panel of morphologies by self-assembly. The structuration of the nanodomains of PPFS/PBuA BCPs were studied by AFM and SAXS. Nanodomain sizes ranging from 30 to 45 nm depending on the molar mass of the BCP were observed. Moreover, the lability of the fluorine atom in para position of the aromatic ring of the PFS units allows for the functionalization of the BCPs. Indeed, the para fluorine-thiol soft organo-catalysed substitution was performed with 1-hexanethiol as side group. The thermal properties and the self-assembly pattern of the BCP changes drastically by the incorporation of alkyl moiety, acting as an artificial increase of the volume fraction of the PPFS block and also matching the solubility parameter value of the PBA block, i.e. no more nano-pattern is observed by AFM and SAXS.